Kecacatan Hukum Perjanjian Jual Beli Vila - Widiyanti, Ikarini Dani; Sari, Nuzulia Kumala; Ayuning Tiyas, Vica Putri (Widya Yuridika, 2024)
The implementation of buying and selling will not always be in accordance with what has been agreed. As an example of the case between Johandi Akman who is consumer and PT.Putra Adhi Prima who is a seller or business actor. In this case the panel of judges in the Cibinong Court Decision Number: 57/Pdt.G/2021/Pn.Cbi on 12 July 2021 stated that PT. Putra Adhi Prima had committed an unlawful act where there were hidden defects in the NE-21 villa that was purchased by Johandi Akman. The formulation of the problem in this writing is; First, how is the validity of the binding sale and purchase agreement (PPJB) of villa NE-21 which contains hidden defects? Second, what are the legal consequences of the binding sale and purchase agreement (PPJB) of villa NE-21 which contains elements of an unlawful act? Third, what are the legal considerations in the decision number. 57/Pdt.G/2021 is in accordance with the provisions of Law Number 8 of 1999 concerning Consumer Protection? The research method used is normative juridical with a statutory and conceptual approach. The results obtained from the research are the invalidity of the binding sale and purchase agreement which contains hidden defects, legal consequences of the binding sale and purchase agreement which contains elements of unlawful acts, so the injured party can claim responsibility for the losses suffered, and the legal considerations in decision number 57/Pdt.G/2021/Pn.Cbi are in accordance with applicable legal provisions.